Effectiveness of four types of bandages and kinesio-tape for treating breast-cancer-related lymphoedema: a randomized, single-blind, clinical trial - Torres-Lacomba, María; Navarro-Brazález, Beatriz; Prieto-Gómez, Virginia; Ferrandez, Jean Claude; Bouchet, Jean Yves; Romay-Barrero, Helena (Clinical rehabilitation, 2020)
To compare the effects of four types of bandages and kinesio-tape and determine which one is the most effective in women with unilateral breast cancer-related lymphoedema. Randomized, single-blind, clinical trial. Physiotherapy department in the Women's Health Research Group at the University of Alcalá, Madrid, Spain. A total of 150 women presenting breast-cancer-related lymphoedema. Participants were randomized into five groups ( = 30). All women received an intensive phase of complex decongestive physiotherapy including manual lymphatic drainage, pneumatic compression therapy, therapeutic education, active therapeutic exercise and bandaging. The only difference between the groups was the bandage or tape applied (multilayer; simplified multilayer; cohesive; adhesive; kinesio-tape). The main outcome was percentage excess volume change. Other outcomes measured were heaviness and tightness symptoms, and bandage or tape perceived comfort. Data were collected at baseline and finishing interventions. This study showed significant differences between the bandage groups in absolute value of excess volume ( < 0.001). The most effective were the simplified multilayer (59.5%, IQR = 28.7) and the cohesive bandages (46.3%, IQR = 39). The bandages/tape with the least difference were kinesio-tape (4.9%, IQR = 17.7) and adhesive bandage (21.7%, IQR = 17.9). The five groups exhibited a significant decrease in symptoms after interventions, with no differences between groups. In addition, kinesio-tape was perceived as the most comfortable by women and multilayer as the most uncomfortable ( < 0.001). Simplified multilayer seems more effective and more comfortable than multilayer bandage. Cohesive bandage seems as effective as simplified multilayer and multilayer bandage. Kinesio taping seems the least effective.